Smart home - Mohd Ali, Nasyrulaizat; Ab Rashid, Muhammad Amirul Adika (2016)
Smart home is project is a simple engineering project that fully hardware project. This project can be controlled using remote controller that can switch ON and OFF electrical appliances using via Infra-red that depends on specific distance. This project also include with the fire alarm system that is designed to ensure safety at home. This project’s aim is to decrease the electric consumption in daily life and to make a safer environment at home from accidents.The main advantage of this project is todevelop program of wireless remote control home appliances. The calculated parameters have been optimized using Proteus 8 Professional software. This software also used to design the circuits of the project. This project using IC such asCD 4017, CD 4013, ULN2003, NE 555 timer. This project consist of their own sensor that work to detect the signal via infra red and detect heat at certain temperature.